Epistemologi Akal Dan Wahyu Dalam Pemikiran Al-Farabi - Saleh, Musyirah; Syamsuddin, Darussalam (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
The issue of the relationship between reason and revelation constitutes a central theme in the epistemology of classical Islamic thought. Al-Farabi, as one of the most prominent Muslim philosophers, sought to synthesize these two domains through a systematic philosophical approach. This study aims to examine the concepts of reason and revelation in Al-Farabi’s thought and to elucidate how their relationship shapes the framework of Islamic epistemology. This research employs a qualitative method with a library-based approach, focusing on Al-Farabi’s primary works and relevant secondary literature. The findings indicate that Al-Farabi regards reason and revelation as two sources of knowledge originating from the same divine source and, therefore, not inherently contradictory. Reason functions as a rational instrument for apprehending truth, while revelation represents divine knowledge received by the prophet through the mediation of the Active Intellect. Al-Farabi’s epistemological framework remains highly relevant for contemporary Islamic thought, particularly in addressing the challenges posed by modernity and the dominance of rationalism.